2008
DOI: 10.1167/iovs.07-1104
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Serum Amyloid A in Glaucoma and Its Effect on Intraocular Pressure

Abstract: These findings indicate that SAA, which is an acute-phase apolipoprotein that plays important roles in infection, inflammation, and tissue repair, may contribute to the pathogenic changes to the TM in glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 34 publications
3
34
0
1
Order By: Relevance
“…In a mouse model of ocular hypertension that assayed gene expression before the onset of retinal cell apoptosis, serum amyloid A (SAA), too, was found to be up-regulated in retinal microglia (Walsh et al 2009). It is interesting in this context that SAA is also up-regulated in the glaucomatous trabecular meshwork (Wang et al 2008a). Microglial activation may be detrimental to ganglion cell survival.…”
Section: Differential Gene Expression In Glaucomamentioning
confidence: 99%
See 1 more Smart Citation
“…In a mouse model of ocular hypertension that assayed gene expression before the onset of retinal cell apoptosis, serum amyloid A (SAA), too, was found to be up-regulated in retinal microglia (Walsh et al 2009). It is interesting in this context that SAA is also up-regulated in the glaucomatous trabecular meshwork (Wang et al 2008a). Microglial activation may be detrimental to ganglion cell survival.…”
Section: Differential Gene Expression In Glaucomamentioning
confidence: 99%
“…Microarray studies of gene expression have been conducted using isolated trabecular meshwork cells, organ cultures, and fresh tissue from a variety of animal models and humans (Gonzalez et al 2000;Ishibashi et al 2002;Lo et al 2003;Vittitow and Borras 2004;Zhao et al 2004;Diskin et al 2006;Liton et al 2006;Rozsa et al 2006;Fan et al 2008;Wang et al 2008a;Danias et al 2011;Liu et al 2013). The conditions assayed in these studies were primaryopen angle glaucoma, elevated pressure, and treatment of trabecular meshwork cells with steroids or TGFb.…”
Section: Differential Gene Expression In Structures Of the Anterior Eyementioning
confidence: 99%
“…Interestingly, TNFR1b ablation affords robust neuroprotection to RGCs in mouse model of elevated IOP. Geneprofiling studies have also indicated upregulation of serum amyloid A which is an inflammatory marker in the trabecular meshwork and retina in human glaucoma [79]. Reduction in Ab-derived neuro-inflammation through minocycline treatment which leads to microglial inhibition has protective effects in AD as well as on the RGCs in glaucoma [6,80].…”
Section: Association With Inflammatory Pathwaysmentioning
confidence: 99%
“…Like other neurodegenerative disorders, deposition of unfolded or misfolded proteins aggregates has been found in RGC of glaucoma patients Janciauskiene and Krakau 2001;Vemuganti and Mandal 2002;Bhattacharya et al 2005;Gupta et al 2008;Wang et al 2008;Wostyn et al 2008;Yin et al 2008). Deposition of cochlin, which is primarily associated with deafness has also been observed in glaucomatous TM cells (Bhattacharya et al 2005).…”
Section: Glaucoma As a Neurodegenerative Disordermentioning
confidence: 99%